Implikatur dalam Novel Lakon karya Ardini Pangastuti BN: Kajian Pragmatik - Listiyani, Arifah; Widodo, Widodo (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2025)
This study examines the forms of implicature in Ardini Pangastuti B.N.'s novel Lakon using a pragmatic approach. Pragmatic analysis of contemporary Javanese novels that integrate wayang cultural values is still limited, so this study fills that gap by systematically examining the types of implicatures in dialogues between characters that reflect implicit communication in the Javanese cultural context. A qualitative descriptive method with content analysis techniques was used to analyze 86 implicative utterances obtained through the read-and-record technique from the novel Lakon. The analysis was conducted using Grice's (1975) implicature theory framework, which distinguishes between conventional, non-conventional (conversational), and presuppositional implicatures. The results of the study show that out of a total of 86 data, 37 (43%) were conventional implicatures, 29 (33.7%) were non-conventional implicatures, and 20 (23.2%) were presuppositions. The dominance of conventional implicatures indicates a tendency toward indirect communication in Javanese culture, which emphasizes politeness and social harmony. This study contributes to the development of pragmatic theory by revealing distinctive implicature patterns in literature rooted in local culture and offers an applicable analytical framework for teaching pragmatics and analyzing Indonesian literary discourse.